The two-faced effects of nerves and neuropeptides in corneal diseases. (January 2022) - Lasagni Vitar, Romina Mayra; Rama, Paolo; Ferrari, Giulio
Abstract: Corneal nerves are instrumental to maintain cornea integrity through regulation of key physiological functions such as tear secretion, blink reflex, and neuropeptide turnover. Corneal nerve injury/stimulation can follow many insults including mechanical/chemical trauma, infections and surgeries. Nerve disruption initiates a process named neurogenic inflammation which leads to edema, pain, and recruitment and activation of leukocytes. Interestingly, leukocyte influx in the cornea can further damage nerves by releasing inflammatory mediators-including neuropeptides. The clinical outcome of neuroinflammation can be beneficial or detrimental to corneal integrity. On one side, it ensures prompt wound healing and prevents infections. On the other, prolonged and/or deranged neuroinflammation can permanently disrupt corneal integrity and impair vision. The cornea is an ideal site to study peripheral neuroinflammation and neurogenic inflammation since it receives the highest density of sensory nerves of the entire body. We will review the corneal nerve anatomy and neurochemistry, discuss the beneficial and detrimental effects of neurogenic inflammation in corneal wound healing, inflammatory processes, and pain. We will also examine the emerging remote impact of corneal nerve disruption on the trigeminal ganglion and the brain, highlighting the key role of neuropeptide Substance P. Finally, we will discuss the clinical relevance of such neuroinflammatory network in the context of severe and highly prevalent ocular diseases, including potential treatments. Graphical abstract: Image 1 Highlights: The cornea is an ideal site to study neuroinflammation and neurogenic inflammation because of its densely innervated. The effects of nerves and neuropeptides in the cornea are two-faced. Targeting neuroinflammatory processes represents an attractive choice to treat multiple ocular surface diseases. Substance P is a key mediator of corneal neuroinflammation, angiogenesis, and pain. Neurokinin-1 receptor antagonists could be useful to treat corneal inflammation and pain.